Jawapan

2016-06-21T03:11:40+08:00
1.      2x + 2y = 7
   (-)  2x + y   = 3
 ∴ 2x-2x=0, so habis. 2y-y=y. 7-3=4.
   y=4
   masukkan y dlm 2x + 2y = 7 / 2x + y   = 3
   cth: 2x + 4 = 3
          2x = -1
            x = 
- \frac{1}{2}

2 .    3a - 4b = - 5
        (a - b = - 3)
×3     → 3a - 3b = -9
         
             
3a - 3b = -9
         (-) 3a - 4b = - 5
        3a-3a habis. - 3b - (-4b) = b. -9-(-5)=-4  → b= -4
        masukkan b= -4 dlm  3a - 4b = - 5 / 3a - 3b = -9
        cth: 
 3a - 3b = -9
                3a = -9 + 3(-4)
                  a = -21